2020
DOI: 10.1089/g4h.2019.0016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exergaming on Balance of Healthy Older Adults: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Balance is critical for older adults to perform daily activities. However, age-related declines in balance increase the risk of falls and severe injuries, such as bone fractures and head injuries. Exergames have been widely applied to improve health-related outcomes in older adults. This meta-analysis aims to quantify the effects of exergaming interventions on balance performance in healthy older adults. A literature search was performed using PubMed, ScienceDirect, SPORTDiscus, COCHRANE, EBSCO, and EMBASE. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 87 publications
3
55
0
Order By: Relevance
“…The systematic review by Hortobágyi et al [ 23 ] reported a similar effect size for MCTPs on the self-selected gait, compared to resistance and coordination training (0.86 vs. 0.84 and 0.76, respectively). On the other hand, some recent studies [ 19 , 29 , 30 ] highlight that physical–cognitive interventions like dancing [ 30 ], exergames [ 31 , 32 ], or the addition of cognitive demands into physical exercise in the so called multicomponent cognitive training programs (MC cog TPs) [ 30 ], are even better strategies to improve both, physical and cognitive outcomes, compared to training programs with an isolated physical capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic review by Hortobágyi et al [ 23 ] reported a similar effect size for MCTPs on the self-selected gait, compared to resistance and coordination training (0.86 vs. 0.84 and 0.76, respectively). On the other hand, some recent studies [ 19 , 29 , 30 ] highlight that physical–cognitive interventions like dancing [ 30 ], exergames [ 31 , 32 ], or the addition of cognitive demands into physical exercise in the so called multicomponent cognitive training programs (MC cog TPs) [ 30 ], are even better strategies to improve both, physical and cognitive outcomes, compared to training programs with an isolated physical capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, exergames allow concurrent physical and cognitive exercise (dual tasking). Recent systematic reviews have demonstrated that exergames improve the physical health (i.e., balance, mobility, physical fitness, and walking performance/gait parameters) and mental health (i.e., executive functions, reaction time, and processing speed) of older adults [ 19 , 20 , 21 ]. Game-based exercises using the Nintendo, Wii Fit, and Xbox Kinect devices have consistently demonstrated positive effects on balance in healthy older adults.…”
Section: Introductionmentioning
confidence: 99%
“…They also often do not allow for comparison of the results in various groups of patients [16]. In a very recent review and meta-analysis [17], authors emphasized the need to develop study designs that utilize biomechanical and other objective measures of balance. Only four out of 16 included papers involved objective evaluation.…”
Section: Introductionmentioning
confidence: 99%